2012
DOI: 10.1021/pr300810f
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the CHO Secretome using Mucin-type O-Linked Glycosylation and Click-chemistry

Abstract: Chinese hamster ovary cells (CHO) are the most common cell line used in the production of therapeutic proteins. Understanding the complex pattern of secreted host cell proteins (HCP) that are released by CHO cells will facilitate the development of new recombinant protein production processes. In this study, we have adapted the N-azido-galactosamine (GalNAz) metabolic labeling method to enable the mass spectrometry identification and quantification of secreted proteins in cell culture media. CHO DG44 and CHO-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 31 publications
2
49
0
Order By: Relevance
“…A recent study used the metabolic labeling strategy with UDP-GalNAz developed by the Bertozzi group (20) to probe the O-glycoproteome of the secretome of CHO DG44 and S cells (10). The study demonstrated that endogenous CHO O-glycoproteins could be identified by this strategy and 352 putative O-glycoproteins were identified in CHO DG44 and CHO S cells, although actual sites of glycosylation were not determined (10).…”
Section: Development Of Cho Simplecells-thementioning
confidence: 99%
See 1 more Smart Citation
“…A recent study used the metabolic labeling strategy with UDP-GalNAz developed by the Bertozzi group (20) to probe the O-glycoproteome of the secretome of CHO DG44 and S cells (10). The study demonstrated that endogenous CHO O-glycoproteins could be identified by this strategy and 352 putative O-glycoproteins were identified in CHO DG44 and CHO S cells, although actual sites of glycosylation were not determined (10).…”
Section: Development Of Cho Simplecells-thementioning
confidence: 99%
“…An improved algorithm for overall prediction of O-glycosylation has recently been introduced (9), but this does not take into account the contribution of individual GalNAc-T isoforms and hence cannot be used to predict the O-glycosylation capacity of particular cells. One recent study identified several O-glycoproteins shed from CHO cells using metabolic labeling with UDP-GalNAz (10), but the identified O-glycoproteins were not characterized further in terms of O-glycan structures and sites. The O-glycoproteome of CHO cells is therefore virtually unexplored.…”
mentioning
confidence: 99%
“…A few efforts have been made to reveal the proteome of CHO spent-media [4,6,7]; however they have never been focused to identify and differentiate packed vs. non-packed proteins though their purpose of origin and mechanism of action towards impacting cell growth and recombinant protein production could be immensely distinct. Besides, differentiation between proteins secreted from healthy cells vs. leaked from damaged or dead cells from packed in microvesicles is also extremely important in designing downstream processing strategies and ultimately to better understand secretome.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a number of growth-regulating factors (such as Fibroblast Growth Factor (FGF), Hepatocyte Growth Factor (HGF), Leukemia Inhibitory Factor (LIF), Vascular Endothelial Growth Factor C (VEGF-C) and transferrin) have been identified in spent-culture media of CHO cells, whose supplementation in the culture media enhances the cell growth in culture (~48%) even at low cell density and improves the performance of production culture [4]. On the other hand, a number of proteolytic enzymes (matrix metallopeptidase 3 (MMP3), MMP10, MMP12 and cathepsin-B) have been identified in culture media which may pose risk for proteolytic-degradation of the product leading to low yield from production batches [5,6]. Besides, efficient removal of these peptides/proteins along with other Host Cell Proteins (HCPs) from the final product during down-stream processing is mandatory for product safety and/or longer shelf-life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation